'Mon cher Fédérico': Fellini and the Cannes Film Festival. Issue 1 (1st January 2021) - Coladonato, Valerio
Between the mid-1950s and the mid-1960s, the Cannes Film Festival contributed to the rise of Federico Fellini's image as an internationally acclaimed Italian auteur. This article situates the relationship between the director and the festival within the respective cultural, industrial and historical contexts. First, it discusses the role of festival director Robert Favre Le Bret in selecting and promoting Italian auteur cinema. Then it focuses on how the system of co-production between Italy and France impacted Fellini's work and the Festival's embrace of his films. Finally, it examines how the French press constructed the image of Fellini as an 'intellectual celebrity'. By grounding the analysis in documents from the Cinémathèque Française (French Film Archive), the Archivio Centrale dello Stato (Central State Archive) in Rome, and other primary sources from both Italy and France, this article provides a synergic view of the conditions for the emergence of Fellini's public image through the Cannes Film Festival.